Project Based Learning Model on Social Studies Learning Motivation - Sri Dewi Nr; Rosleny B; Muhajir M (Indonesian Journal of Primary Education, 2022)
Lack of student learning motivation because they often talk to their classmates. In addition, the learning process used by the teacher is less varied due to the limitations of the learning media owned by the school. In addition to learning media that are less varied, the method used in the learning process tends to use the lecture method because with this method it is considered that students will more easily accept the material presented. Such conditions certainly make the learning process only mastered by the teacher. This study aims to determine whether there is an effect of project-based learning model on social studies learning motivation of students of Class V MI Wahyu Mandiri, Pallangga District, Gowa Regency, where Class V MI Wahyu Mandiri is the experimental class and Class V MI Al Muhajirin is the control class. This research is a quantitative research model with a quasi-experimental type of research. The population in this study were 15 students of class V MI Wahyu Mandiri as the experimental class and 15 students of class V MI Al Muhajirin as the control class. This type of data collection uses a motivational questionnaire to measure learning motivation. The data analysis technique used is the Manova test, which was previously tested for normality and homogeneity. The results of this study indicate that the implementation of the Project Based Learning learning model in social studies subjects can increase student activity and motivation. This is evidenced by the average in the experimental class 81.07 with a very high category and 78.53 in the control class with a high category. This result can be seen from the motivational questionnaire manova test which obtained the value of sig. 0.00 0.05 (smaller than 0.05) with a 95% confidence level, then Ho is rejected and Ha is accepted, meaning that there is an effect of the Project Based Learning learning model on the learning motivation of fifth grade students at MI Wahyu Mandiri. So, it can be concluded that the Project Based Learning learning model has an influence on the social studies learning motivation of the fifth grade students of MI Wahyu Mandiri.